2015
DOI: 10.1080/08957347.2014.1002922
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Changing Content on IRT Scaling Methods

Abstract: Equating test forms is an essential activity in standardized testing, with increased importance with the accountability systems in existence through the mandate of Adequate Yearly Progress. It is through equating that scores from different test forms become comparable, which allows for the tracking of changes in the performance of students from one year to the next. This study compares three different item response theory scaling methods (fixed common item parameter, Stocking & Lord, and Concurrent Calibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Bias depends on the sample size (Hanson & Béguin, 2002; Kang & Petersen, 2012), the number of items with parameters available from previous calibrations (e.g., Arai & Mayekawa, 2011; Kim, Cole, & Mwavita, 2018), the amount of cross‐national DIF (Sachse, Roppelt, & Haag, 2016), and shifts in the latent ability distributions across assessments (e.g., Baldwin, Baldwin, & Nering, 2007; Keller, Keller, & Baldwin, 2007). Keller and Keller (2011, 2015), however, showed that FIPC works best for complex changes in the latent ability distributions and in cases where the content of the assessment changes. Zhao and Hambleton (2017) showed that FIPC was robust against ability shifts across two adjacent assessments.…”
Section: Purpose Of the Study And Research Questionsmentioning
confidence: 99%
“…Bias depends on the sample size (Hanson & Béguin, 2002; Kang & Petersen, 2012), the number of items with parameters available from previous calibrations (e.g., Arai & Mayekawa, 2011; Kim, Cole, & Mwavita, 2018), the amount of cross‐national DIF (Sachse, Roppelt, & Haag, 2016), and shifts in the latent ability distributions across assessments (e.g., Baldwin, Baldwin, & Nering, 2007; Keller, Keller, & Baldwin, 2007). Keller and Keller (2011, 2015), however, showed that FIPC works best for complex changes in the latent ability distributions and in cases where the content of the assessment changes. Zhao and Hambleton (2017) showed that FIPC was robust against ability shifts across two adjacent assessments.…”
Section: Purpose Of the Study And Research Questionsmentioning
confidence: 99%
“…If equating studies vary the δ or sometimes the θ distribution, then mostly to challenge the equity requirement, in the form of a shift of the mean, i.e., simulating change or growth, as in Kopp and Jones (2020), Han et al (2012), He et al (2013), or Waterbury and DeMars (2021). The skewness of the distribution of the θ parameter is also sometimes varied, but by preserving good targeting, that is, with overlapping dispersion of the δ and θ , as in Manna and Gu (2019) or Keller and Keller (2015). In any case, Suanthong et al (2000) mention, citing L.…”
Section: Introductionmentioning
confidence: 99%